PENGARUH TATA KELOLA PERUSAHAAN DAN KESEMPATAN INVESTASI TERHADAP BIAYA HUTANG DAN STRUKTUR MODAL (Studi Empiris pada Perusahaan Industri Infrastruktur yang Terdaftar di Bursa Efek Indonesia Tahun 2011-2016) - Fazilla, Umi; Halim, Edyanus Herman; Fathoni, Ahmad Fauzan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study is motivated by many inconsistencies of previous research and the lack of related research conducted on the industrial infrastructure firms. This study aims to analyze the effect of good corporate governance (GCG) and investment opportunity set (IOS) towards cost of debt (COD) and capital structure (DER). Path analyze was used to analyze data. Using 22 sample of industrial infrastructure companies listed in Indonesia Stock Exchange from 2011-2016, the result showed that good corporate governance had a negative and not significant impact toward cost of debt, however investment opportunity set had a negative and significant impact toward cost of debt. Good corporate governance had a positive and not significant impact toward capital structure (DER), however investment opportunity set had a positive and significant impact toward capital structure (DER). Furthermore this study found that cost of debt did not intervene the effect of good corporate governance and investment opportunity set toward capital structure (DER).Key Words : Good corporate governance (GCG), investment opportunity set (IOS), cost of debt (COD), capital structure (DER).